Randomised controlled trial of an interactive multimedia decision aid on hormone replacement therapy in primary care. - Murray, E; Davis, H; Tai, S; Coulter, A; Gray, A; Haines, A (2001)
OBJECTIVE: To determine whether a decision aid on hormone replacement therapy influences decision making and health outcomes. DESIGN: Randomised controlled trial. SETTING: 26 general practices in the United Kingdom. PARTICIPANTS: 205 women considering hormone replacement therapy. INTERVENTION: Patients' decision aid consisting of an interactive multimedia programme with booklet and printed summary. OUTCOME MEASURES: Patients' and general practitioners' perceptions of who made the decision, decisional conflict, treatment choice, menopausal symptoms, costs, anxiety, and general health status. RESULTS: Both patients and general practitioners found the decision aid acceptable. At three months, mean scores for decisional conflict were significantly lower in the intervention group than in the control group (2.5 v 2.8; mean difference -0.3, 95% confidence interval -0.5 to -0.2); this difference was maintained during follow up. A higher proportion of general practitioners perceived that treatment decisions had been made "mainly or only" by the patient in the intervention group than in the control group (55% v 31%; 24%, 8% to 40%). At three months a lower proportion of women in the intervention group than in the control group were undecided about treatment (14% v 26%; -12%, -23% to -0.4%), and a higher proportion had decided against hormone replacement therapy (46% v 32%; 14%, 1% to 28%); these differences were no longer apparent by nine months. No differences were found between the groups for anxiety, use of health service resources, general health status, or utility. The higher costs of the intervention were largely due to the video disc technology used. CONCLUSIONS: An interactive multimedia decision aid in the NHS would be popular with patients, reduce decisional conflict, and let patients play a more active part in decision making without increasing anxiety. The use of web based technology would reduce the cost of the intervention.